Adaptation of Students to the Higher Education Environment and Personality Development - Urayimova Muqaddam Komiljon Qizi (Academia Open, 2026)
General Background: Adaptation to the higher education environment represents a complex socio-psychological process shaping students’ academic and personal trajectories. Specific Background: This study analyzes students’ adaptation in relation to psychological conditions such as stress, anxiety, motivation, and self-esteem within academic and social contexts. Knowledge Gap: Despite extensive discussions, the interrelationship between socio-psychological adaptation and personality development within higher education environments remains insufficiently integrated. Aims: The study aims to identify socio-psychological characteristics of student adaptation and examine their relationship with personality development. Results: Findings indicate that students with higher adaptation levels demonstrate better stress management, sustained motivation, and development of qualities such as independence, responsibility, social activity, communication culture, and self-awareness, with strong positive correlation between adaptation and personality development supported by empirical data. Novelty: The study provides an integrated analysis linking academic and social adaptation processes with psychological states and personality formation using combined theoretical and empirical approaches. Implications: The results offer a scientific basis for developing practical recommendations to support student adaptation, strengthen psychological stability, and optimize pedagogical interactions in higher education institutions, contributing to improved academic and personal outcomes. Highlights:• Strong Correlation Identified Between Adjustment Level and Individual Growth Traits• Psychological States Such as Anxiety and Motivation Linked With Adaptation Patterns• Social Support and Group Interaction Recognized as Key Developmental Drivers Keywords: Higher Education Environment, Student Adaptation, Personality Development, Socio-Psychological Adaptation, Psychological State